Analytical Molecular Biology : Quality and Validation. - Bedson, Peter (Valid Analytical Measurement., 1999)
In spite of the wide variety and complexity of biological materials, nucleic acids are ubiquitous. DNA is becoming the bioanalyte of choice due to the vast amount of information embedded in its sequence, its robust chemical nature and the range of highly sensitive analytical techniques that have been developed. The results of such analyses can have an important impact on our society both commercially and in terms of the quality of life. Absolute confidence in the data generated is therefore of the utmost importance. This book, produced by LGC as part of the VAM (Valid Analytical Measurement) P.